Effect of Chilled Ageing Conditioning at 4°C in Lamb Longissimus Dorsi Muscles on Water-Soluble Flavour Precursors as Revealed by a Metabolomic Approach. (2nd September 2019) - You, Liqin; Luo, Ruiming
Abstract : The objective of this study was to investigate, by a metabolomic approach, the effects of chilled ageing conditioning at 4°C in lamb longissimus dorsi (LD) muscles on water-soluble flavour precursors. The results showed that the content of nucleotide degradation products significantly increased (P < 0.05 ) due to the adjusted biosynthesis of alkaloids derived from histidine and purine from day 0 to day 4. Additionally, the content of glycolytic compounds significantly increased (P < 0.05 ) due to enhanced glycolysis, and the content of organic acid increased (P < 0.05 ) because of the altered tricarboxylic acid cycle (TCA) from day 0 to day 4. In addition, the content of total free amino acids significantly increased (P < 0.05 ), owing to the altered biosynthesis of amino acids from day 4 to day 8. These results are significant proof that there were quantitative changes observed in lamb flavour precursors during chilled ageing.